Orality, Literacy, Modernity and Modern African Poetry - Olugbemi-Gabriel, Olumide (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
This paper attempts to locate and situate how Modem African Poetry turned the corner from a beginning encapsulated in poetic lines which are influenced and modeled after Western style and poets, to embracing forms of African oral traditions. The game changer for modern African poetry is p’Bitek’s Song of Lawino which privileges his people’s oral tradition forms as manifested in songs, proverbs and oral poetry oyer conventional western poetic forms. Osundare’s Villages Voicesequally concretises the achievement of the modern African poet in using the hands of literacy to drag orality to the podium of modern poetic manifestations, The efforts of p’Bitek and Osundare are singled out for praise for their abilities to locate the critical interface between orality and literacy in a better understanding of the consequence of the fatal collision between African oral tradition and ",’estern education which births modern African poetry.